Aerobic Exercise Therapy in Ambulatory Patients With ALS: A Randomized Controlled Trial. (February 2019) - van Groenestijn, Annerieke C.; Schröder, Carin D.; van Eijk, Ruben P. A.; Veldink, Jan H.; Kruitwagen-van Reenen, Esther T.; Groothuis, Jan T.; Grupstra, Hepke F.; Tepper, Marga; van Vliet, Reinout O.; Visser-Meily, Johanna M. A.; van den Berg, Leonard H.
Background: Weakness caused by motor neuron degeneration in amyotrophic lateral sclerosis (ALS) may result in avoidance of physical activity, resulting in deconditioning and reduced health-related quality of life (HRQoL).Objective: To study the effectiveness of aerobic exercise therapy (AET) on disease-specific and generic HRQoL in ambulatory patients with ALS.Methods: We conducted a multicenter, assessor-blinded, randomized controlled trial. Using a biphasic randomization model, ambulatory ALS patients were assigned (1:1) to AET+usual care (UC), or UC. AET consisted of a 16-week aerobic cycling exercise program. Primary outcome measures were the 40-item ALS assessment questionnaire (ALSAQ-40), and the mental component summary (MCS) and physical component summary (PCS) scores of the short-form survey (SF-36), using linear mixed effects models. Per-protocol (PP) analysis was performed for those patients who attended ≥75% of the training sessions; controls were matched (1:1) by propensity score matching.Results: Of 325 screened patients, 57 were randomized: 27 to AET+UC and 30 to UC. No significant mean slope differences between groups were observed for ALSAQ-40 (-1.07; 95% confidence interval [CI] -2.6 to 0.5, P =0.172) nor for SF-36 MCS (0.24; -0.7 to 1.1, P =0.576) or PCS (-0.51; -1.4 to 0.38, P =0.263). There were no adverse events related to the AET. PP-analyses showed significantly less deterioration in ALSAQ-40 (-1.88, -3.8 to 0.0, P =0.046) in AET+UC compared to UC.Conclusions: AET+UC was not superior to UC alone in preserving HRQoL in ambulatory ALS patient. However, the study was unfortunately underpowered, because only 10 patients completed the protocol. AET+UC may preserve disease-specific HRQoL in slow progressors.Clinical trial registration number: Netherlands National Trial Register (NTR): 1616.